X‐ray spectroscopic study of chemical state in uranium carbides. (27th January 2022) - Butorin, Sergei M.; Bauters, Stephen; Amidani, Lucia; Beck, Aaron; Weiss, Stephan; Vitova, Tonya; Tougait, Olivier
Abstract : UC and UMeC2 (Me = Fe, Zr, Mo) carbides were studied by the high‐energy‐resolution fluorescence detected X‐ray absorption technique at the U M 4 and L 3 edges. The data were analyzed using the Anderson impurity model. Abstract : UC and UMeC2 (Me = Fe, Zr, Mo) carbides were studied by the high‐energy‐resolution fluorescence‐detected X‐ray absorption (HERFD‐XAS) technique at the U M 4 and L 3 edges. Both U M 4 and L 3 HERFD‐XAS reveal some differences between UMeC2 and UC; there are differences also between the M 4 and L 3 edge results for both types of carbide in terms of the spectral width and energy position. The observed differences are attributed to the consequences of the U 5 f, 6 d –4 d (3 d ) hybridization in UMeC2 . Calculations of the U M 4 HERFD‐XAS spectra were also performed using the Anderson impurity model (AIM). Based on the analysis of the data, the 5 f occupancy in the ground state of UC was estimated to be 3.05 electrons. This finding is also supported by the analysis of U N 4, 5 XAS of UC and by the results of the AIM calculations of the U 4 f X‐ray photoelectron spectrum of UC.